Noopept: development and validation of UV-spectrophotometric determination - Antypenko, Lyudmyla; Burlaka, B. S.; Belenichev, I. F.; Антипенко, Людмила Миколаївна; Бурлака, Богдан Сергійович; Бєленічев, Ігор Федорович (Харків : НФаУ, 2017)
Introduction: Noopept, ((S)-N-phenylacetyl-L-prolylglycine ethyl ester) is an original peptide drug with nootropic and neuroprotective activity, 200-50000 times more potent, than piracetam, also effective for the treatment of psychoor-ganic disorders with cerebroasthenic and cognitive disturbances in doses of 15 and 30 mg per day. The activation of NMDA receptors was involved in the ef-fects of its single injection, whereas activation of quisqualate/AMPA receptors was associated with the decrease in their efficacy after repeated usage of drug. Among the structural elucidations and determinations, there were reported UPLC–ESI–MS, GC–MS (EI), LC–QTOF–MS (PDA), 1H, 13C NMR, HMQC, HMBC, DQF-COSY and ROE spectra. Still simple UV-spectrophotometric method for common laboratory was not presented in the literature data.
Keywords: тези